Gambaran Perilaku Pencegahan Covid-19 - Ninuk Setyaningati; Wahyu Yusianto (Universitas Ngudi Waluyo, 2022)
One way to prevent the spread of COVID-19 is by administering a vaccine. The government's first vaccine administration program was one of the nurse's health workers. a vaccination strategy and operational plan to close the immunization gap and reach everyone with life-saving vaccines. Efforts to achieve the goals of various programs based on Primary Health Care have been implemented to improve health status. Several indicators are used by WHO to measure the level of success of these programs. The health indicator in the 2030 Sustainable Development Goals (SDGs) which is the third goal, namely health insurance and health promotion for all ages. This study aims to provide an overview of the behavior of Covid-19 prevention in patients in the Maranatha 1 room at Mardi Rahayu Kudus Hospital. The type of design in this research is descriptive research. the number of samples in this study 32 respondents. With Test frequency distribution analysis. The results of the study can be seen that the age of the majority of respondents is 36-50 years, namely 18 respondents (56.3%), while the minority > 50 years, namely 4 respondents (12.5%). While the education of the majority of respondents was junior high school, 11 respondents (34.4%), while the minority was undergraduate, 3 respondents (9.4%). 27 respondents (84.4%) had good preventive behavior for Covid-19 patients, while 5 respondents (15.6%) had a bad minority. The majority of the descriptions of the preventive behavior of Covid-19 patients in the Maranatha 1 room at Mardi Rahayu Kudus Hospital are good.ABSTRAKSalah satu pencegahan penyebaran covid 19 yaitu dengan pemberian vaksin. Program pemerintah pemberian vaksin yang pertama diberikan yaitu salah satunya tenaga kesehatan perawat. strategi vaksinasi dan rencana operasional untuk mengatasi kesenjangan imunisasi dan menjangkau setiap orang dengan vaksin yang menyelamatkan jiwa. Upaya untuk mencapai tujuan berbagai program dengan berbasis Primary Health Care telah dilaksanakan untuk meningkatkan derajat kesehatan. Beberapa indikator yang digunakan WHO untuk mengukur tingkat keberhasilan program program tersebut. Indikator kesehatan dalam Sustainable Development Goals (SDGs) 2030 yang merupakan goals ketiga yaitu jaminan kesehatan dan promosi kesehatan bagi semua umur. Penelitian ini bertujuan Untuk mengetahui gambaran tentang perilaku pencegahan covid-19 pada pasien di ruang Maranatha 1 Rumah Sakit Mardi Rahayu Kudus. Jenis rancangan dalam penelitian ini adalah penelitian deskriptif. jumlah sampel pada penelitian ini 32 responden. Dengan Uji analisa distribusi frekuensi. Hasil penelitian dapat dilihat bahwa umur respondeen mayoritas 36-50 tahun yaitu 18 responden (56.3%), sedangkan yang minoritas >50 tahun yaitu 4 responden (12.5%). Sedangkan pendidikan responden mayoritas SMP 11 responden (34.4%), sedangkan minoritas Sarjana 3 responden (9.4%) . perilaku pencegahan pasien covid-19 mayoritas baik 27 responden (84.4%), sedangkan minoritas buruk 5 responden (15.6%). Gambaran perilaku pencegahan pasien covid-19 di ruang Maranatha 1 Rumah Sakit Mardi Rahayu Kudus mayoritas baik.